Suppressio e surrectio: natureza, efeitos, aplicabilidade e análise comparativa com figuras jurídicas correlatas - Paula, Luiza Checchia Stuart Cunha de (2015)
The paper analyzes the institutes of surrectio and suppressio, differentiating them from related figures, demonstrating its practical applicability and discussing questions on the topic. First of all, it analyzes the principles of good faith and trust, whose understanding it is deemed essential to the understanding of the topic. Examines the objective good faith focused on sealing the contradictory behavior, and in the famous theory of proper actions. Traces a historical context of the suppression of contradictory behavior, showing the evolution of the need to protect trust as the foundation of existence of a legal relationship. Studies the origin of the concepts of suppressio and surrectio, conceptualizes institutes and characterized their assumptions of existence and of the appropriateness of its assumptions. Discusses the concept and the applicability of other figures arising from the principle that prohibits the contradictory behavior and their chances of appropriateness, bringing its implementation in doctrine and jurisprudence. Studies the effects of suppressio and surrectio and the distinction of the practical application in relation to prescription, estoppel, novation and similar institutes. Shows the current scenario of the use of these figures by the operators of Brazilian law, as well as other institutes, based on analysis of relevant judgments by Brazilian Courts